PHYSICOCHEMICAL CHARACTERISTICS OF ECO-ENZYME DERIVED FROM DURIAN ALBEDO AS A SOLUTION FOR WASTE MANAGEMENT - Harahap, Doli Fadly; Ayu, Gabriella Marry; Putri, Syarifah Riska Mela (Universitas Negeri Medan, 2024)
North Sumatra is the largest durian-producing province in Indonesia. As a result, durian skin waste has increased, reaching 332,712 tons annually. Durian skin is divided into the outer layer, known as the flavedo and the inner layer called the albedo. Durian skin contains chemical compounds such as lignin and tannins, which hinder its efficient decomposition. Therefore, environmentally friendly solutions for processing durian skin waste are needed. One such solution is the production of eco-enzyme. Eco-enzyme is a complex solution produced by fermenting organic waste with molasses and water, using selective microorganisms. It has various applications, such as household cleaners, organic fertilizers, and pest control. The purpose of this study was to identify the physicochemical characteristics and quality of the eco-enzyme produced, as well as its potential to reduce environmental pollution. The research employed a descriptive qualitative method with an experimental approach. The process involved coarsely chopping durian albedo and mixing it with molasses and water in a 1:3:10 ratio (sugar, albedo, and water). The mixture was fermented for three months, sealed tightly in a container, and periodically opened. The resulting liquid was the eco-enzyme. Physicochemical tests were conducted to evaluate pH, aroma, color, total dissolved solids (TDS) and other properties, including Wagner's Reagent test, Alkaline Reagent test, Foam test, and Quinone test. The results showed that durian albedo is highly suitable for producing eco-enzyme, yielding a product with a pH of 2.4, a TDS value of 855, a blackish-brown color, a fruity fermentation aroma, and containing phytochemical compounds such as alkaloids, flavonoids, saponins, and quinones.